Food partitioning among fishes in Pahang River-estuary, Malaysia - Mohamed, Ahmad Azfar; Khan Chowdhury, Ahmed Jalal; Abdurahman, Siti Waznah (Universiti Teknologi Malaysia, 2015)
A study was conducted on the food resource partitioning among fish species in Pahang River-estuary from 2010-2013 during pre-monsoon and post-monsoon period. The area was divided in three strata (upstream, downstream and middle zone), based on environmental features. Stomach contents of all species present were analyzed. From 138 of total stomach analyzed, 24 of them were empty and 114 were with food. From the analysis of prey in the stomachs, various kinds of food items consumed by the different size of fishes included phytoplankton, zooplankton, unidentified materials, fish, fish parts, shrimp, shrimp parts, crab, crab parts, plant parts, mollusk and detritus. Detritus consisted of all types of biogenic materials in various stages of microbial decomposition. Different fishes consume different types of food and feeding habit of fishes varies from season to season. From the percentage of number and occurrence of food resources, zooplankton are important in their own right as a major component of fish diets and are especially important to small and young individuals, even for the detrivore. Nevertheless, it represents an important trophic resource for fish food web of Pahang River-estuary.